(3LGeY GdCUhd dCMGOjK GdQShds - (3GdeHGQc Hf eMeO Hf eMeO Hf eMeO Hf nYrHO GdncpQje GdTjHGfqj GdLRQj, CHh GdSYGOGJ, eLO GdOjf, GHf GdCKjQ,J (B606 (3g` s ((3CMeO Hf YHO GdhGMO Hf GdMGL jhSa s)
(3ChdgG (B:s
(3GdMeO ddg GdPi ChVM deYGde GdESdGe SHjdG CeG HYO aEf eHfi gPG GdcJGH Ydi KdGKI CQcGf GdChd ai GdeHGOi s
(3BNQgG (B:s
(3hbO LGA ai cJGH GdJQePi (B: (3dbO HJfG djdJfG gPg hMTi cCfg bGd LeGYI hMTi gPg hGdMeO ddg Ydi MSf Jhajbg s
(3GdeLdO GdKGfi egRhRs
(3HgG fXGe GdJYbjHI HChd GdLRA GdChd SeGY Ydi eMehO Hf eSYhO bWH GdOjf GdTjQGRi SfI (B707s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B272 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B174s
Keywords: (3GdMOjK h GdeUWdMs